Ladybird read with me : picture dictionary (contains 100 key words) - Matthews, Anne (Ladybird Books Ltd Loughborough, 1993)
A picture dictionary, which is part of a reading scheme intended to cover the three main methods of teaching reading. Its publication coincides with the launch of the new phonic scheme "Say the Sounds" and has a simplified message to parents.